Effects of the turn-back primer on intermediate product generation in isothermal DNA amplification. (December 2010) - Tanaka, Yuki; Kimura, Yasumasa; Mitani, Yasumasa; Kawai, Yuki; Lezhava, Alexander; Noma, Shohei; Tagami, Michihira; Kawai, Jun; Hayashizaki, Yoshihide; Usui, Kengo
In DNA amplification, the initial step of copying a target sequence from the template DNA, or the so-called intermediate product generation step, is very important. In examining the turn-back primer (TP)–dependent isothermal DNA amplification (TIA) method, we determined the actual time point of intermediate product generation by extrapolating dsDNA amplification curves. Our results indicate that intermediate product creation is the rate-limiting step in TIA, and good TP design is advantageous for improving the intermediate production process.